Analisis dan Desain Sistem Informasi Manufaktur di PT. XYZ - Halim, Denny Iswanto (Kajian Ilmiah Mahasiswa Manajemen, 2015)
The dynamic condition of businesses environment and the rapid growth of computer technology and information encourage the industry to make changes and increase their productivity to survive. Manufactur Information System is a part of Management Information System which is a company activity support which can give company competitive advantage to make quick response, as a decision support tools and make lean production. This qualitative research using case study approach to explore and identify Manufactur Information System in PT. XYZ. Data gathering is held by filling-in questionaire and interviewing 5 key person (informers) that are intensively involved in production operational and company information system, and a fieldwork to get the daily operation detail. The data was analyzed with describe process flow, document flow, data flow and entity relationship from company process manufactur. The result of questionnaire, interviews and field work interpretation shows that manufactur information system process is very complex, so need to describe the wholly process to facilitate in process development system.